Cannabis use patterns among people with HIV before and after legalization - AW Hahn; SA Ruderman; RM Nance; JAC Delaney; BM Whitney; S. Eltonsy; L. Haidar; LN Drumright; J. Ma; KH Mayer; C. O’Cleirigh; L. Bamford; et al. (Drug and Alcohol Dependence Reports)
Background: Cannabis use is highly prevalent and detrimental among people with HIV (PWH). Legislative changes in several states altered the legality and accessibility of cannabis. We examined pre-post legislative changes in current, daily, and severe use in PWH in clinical care. Methods: PWH engaged in the Centers for AIDS Research Network of Integrated Clinical Systems (CNICS) cohort from 3 sites/states were asked about past 3-month cannabis use on a routine clinical assessment of health behavior before and after legalization. A fourth site in a state without legalization served as a comparator. We used linear regression to estimate changes in use prevalence from 1 year before to 1 year after legalization. Results: Among PWH (n=7885), from 1 year before to 1 year after legalization, cannabis use prevalence increased slightly in Boston, MA (32–38 %), Birmingham, AL (26–27 %), and San Diego, CA (25–29 %); and decreased in Seattle, WA (44–41 %). Contemporaneously, daily cannabis use increased modestly (less than 5 %) at all sites. Severe use (cannabis-specific ASSIST score ≥27) decreased or plateaued at all sites. No site showed significant change in prevalence trends of current, daily, or severe use 1 year before and after legalization in linear regression (p >0.05). Conclusion: Few changes prevailed in cannabis use patterns around dates of legalization among PWH in care in the U.S. Relaxation of cannabis policy does not appear to result in an immediate increase in use among PWH.